Proximate analysis of gluten-free milk boosting cookies containing banana flowers - Haron, Normah; Mohamad Yusof, Nurul Izzaty (Malaysian Institute of Chemistry, 2021)
The World Health Organization (WHO) suggests that mothers should exclusively breastfeed their babies for the first two years after birth. Musa paradisiacaflowers, also known as banana flowers, have traditionally been consumed by mothers in Malaysia for its milk-boosting effect (the galactagogue effect). In this study, banana flower-based lactation cookies were formulated using three gluten-free flours, namely tapioca flour, rice flour and potato starch. Proximate analysis of these cookies were evaluated for their ash, moisture, protein, fat, crude fibre, carbohydrate and caloriccontent. Analysis was performed according to AOAC standard methods (dry ashing, hot air-oven drying, Kjeldahl nitrogen digestion, and Soxhlet-extraction). The results showed that the cookies made from rice flour had the highest nutritional content in terms of protein, fat and calories (12.29%, 54.14% and 54.03 kcal, respectively). The nutritional content of all three types of cookies showed significant differences (p<0.05) except in the case of ash content. A comparison with commercially available lactating cookies (fenugreek-based) showed that the Musa paradisiacaflower cookies contained higher levels of fibre, fat, and carbohydrate (p<0.05). However, the commercialized cookies had a higher calorie content (180 kcal) compared to our cookies (54.03 kcal). In conclusion, cookies made with Musa paradisiaca and rice flour were found to have a higher nutritional content than commercially available cookies and should be further researched for its effects on milk production in lactating mothers.